La eficacia de un Grupo de Encuentro Gestáltico medida con el POI (Personal Orientation Inventory) - Castanedo, Celedonio (INFORMACIO PSICOLOGICA)
The present study introduce the Personal Orientation Inventory (POI) as psychological instrument that measures Self-Actualization defined by Maslow, Rogers, and Perls as a measure of positive mental health. The POI was applied to two groups: an experimental group, -that follow an Encounter Group of 12 hours centered in Gestalt Therapy-, composed of fifteen people (9 women and 6 men); and a control group with the same number of subjects and gender, in three moments: pretest, posttest, post-postest. The results indicated significant changes in the mean score of the experimental group in two Scales of the POI: TC (Time Competence) and I (Inner Directed), and the sum of both scales (TC + I). There were no significant changes in the control group.